2019
DOI: 10.2298/botserb1901097t
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovery of Chara canescens Loiseleur in Serbia

Abstract: Chara canescens is the only charophyte performing parthenogenetic reproduction. Although most recently found populations consist solely of parthenogenetically reproducing females, bisexual populations exist as well, making the species a unique example of the sympatric occurrence of both reproductive modes. In Serbia, C. canescens was found only once for certain, near Prokuplje in 2005. The purpose of the present study is to report a reliable new finding of C. canescens in Serbia, in a stable parthenogenetic fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…8.2) is partially bordered by the Tamiš River in the south, and all along the western border by the Tisa River, this area is generally arid, especially the northern part, and characterized by unique saline SSWB of both natural and artificial origin. All charophyte records in this region (Table 8.2), except the recent findings of C. canescens [92], are old and have not been confirmed by Vesić [88] in the latest systematic survey of this region. Recordings were made in only four localities near Ečka, Čenta, Kikinda, and Zrenjanin, and prevalently in various types of ponds [87].…”
Section: Macroalgae In Vojvodinamentioning
confidence: 79%
See 1 more Smart Citation
“…8.2) is partially bordered by the Tamiš River in the south, and all along the western border by the Tisa River, this area is generally arid, especially the northern part, and characterized by unique saline SSWB of both natural and artificial origin. All charophyte records in this region (Table 8.2), except the recent findings of C. canescens [92], are old and have not been confirmed by Vesić [88] in the latest systematic survey of this region. Recordings were made in only four localities near Ečka, Čenta, Kikinda, and Zrenjanin, and prevalently in various types of ponds [87].…”
Section: Macroalgae In Vojvodinamentioning
confidence: 79%
“…8.2), the following review will focus on Special Nature Reserve (SNR) "Gornje Podunavlje", as charophyte studies mainly took place in this protected area particularly. The only record made out of this protected area is the record of Chara canescens in channel Vrbas-Bezdan, near Mali Stapar [97], but this record is challenged by later authors [88,92] and will not be considered in this review. SSWB in SNR "Gornje Podunavlje" are very rich in charophyte diversity [88, 90, A literature overview reveals even 21 localities where charophytes were detected, among which ponds are the habitats where most of the charophyte records were made and where the highest diversity was recorded [88,90,93].…”
Section: Macroalgae In Vojvodinamentioning
confidence: 99%
“…Only female plants were found, which is typical for this species since most of the populations in Europe do not contain any male shoots, but only parthenogenetic females (Schaible et al 2011). Trbojević et al (2019) also found only female plants.…”
mentioning
confidence: 77%
“…However, in 2018 it was rediscovered in an excavation pond made in the process of clay digging in Plava banja near Kikinda. The pond is eutrophic and with extreme ion concentrations, used as a source of drinking water for cattle (Trbojević et al 2019). The finding in the Kilapoš waterhole is hence the second record for Serbia.…”
mentioning
confidence: 98%
See 1 more Smart Citation